Multifunctional Li(Ni0.5Co0.2Mn0.3) O2-Si batteries with self-actuation and self-sensing. (April 2020) - Ma, Jun; Gonzalez, Cody; Huang, Qingquan; Farese, Joseph; Rahn, Christopher; Frecker, Mary; Wang, Donghai
Among anode materials for Li-ion batteries, Si is known for high theoretical capacity, low cost, large volume change, relatively fast capacity fade and significant stress-potential coupling. This article shows that a Li(Ni0.5 Co0.2 Mn0.3 )O2 -Si battery can store energy, actuate with Si volume change and sense with stress-potential coupling. Experiments are conducted in an electrolyte-filled chamber with a glass window withLi ( N i 0 . 5 C o 0 . 2 M n 0 . 3 ) O 2 cathodes and Si composite anodes. The Si anodes are single-side coated on Cu current collector with Si nanoparticles, polyacrylic acid binder and conductive carbon black in a porous composite structure. During charging, the battery stores energy, Li inserts in the cantilevered Si anodes and the cantilevers bend laterally. Discharging the battery releases the stored energy and straightens the Si cantilevers. Imposing deformation on the Si cantilevers at a fixed state of charge causes bending stress in the composite coating and a change in the open circuit potential. Testing at1 Hz confirms that the Si composite responds to dynamic stress variations and with almost no phase lag, indicating the bandwidth of the stress-potential coupling in Si composite anodes is at least1 Hz .